Indirect and direct Chapelle's methods for the determination of lime consumption in pozzolanic materials - Quarcioni,V. A. (2015)
In this work, comments are made about indirect methods and direct Chapelle's method applied to the determination of the reactivity of pozzolanic materials. The Chapelle's method is based on the lime-pozzolan reaction and quantifies the pozzolanic reactivity of any material intended to be applied by the cement industry. This lime consumption determination by the pozzolan through this reaction can be made with mass proportions - lime:pozzolan 1:1, as originally proposed by Chapelle or 2:1, as specified in Brazilian and French Standards. Comparative results with both proportions are presented for sugar cane bagasse ash, rice rusk ash, silica fume, fly ash, and metakaolin, commonly studied in our country. Statistical calculations showed that for some materials of similar characteristics to the researched RHA, FA e MK at issue, essays carried out with only 1g of CaO may be underestimating the amounts of CaO consumed per gram of pozzolanic material that can be obtained. Comments were made about the Brazilian and French Standards based on this method and emphasized the expression of lime consumption per mass of the amorphous phase of these materials, as determined by X ray diffraction analysis with the Rietveld refinement method.